Postharvest Technology of Fruits and Vegetables: An Overview - Singh, Vishal; Hedayetullah, Md; Zaman, Parveen; Meher, Jagamohan (Journal of Postharvest Technology, 2014)
Harvested fruits and vegetables require adequate and advanced  postharvest processing technologies for minimizing the  qualitative as well as quantitative losses after harvesting. Nearly  40% fruits and vegetables are wasted every year due to improper  handling, storage, packaging, and transportation. Wastage of  fruits and vegetables in huge amount due to un-implementation of  advance postharvest technological approaches also reduces the  per capita availability of fruits and vegetables. Intensive emphasis  is required to develop the advance postharvest technologies for  improving the global food security by enriching the economy of  agricultural produce of the world with minimal losses of  consumable fruits and vegetables. The present article discusses  the common yet important postharvest technologies to maintain  the quality of fruits and vegetables.
Keywords: Post-harvest loss; Fruits and vegetables; Postharvest handling; Storage Packaging